2014
DOI: 10.1007/s10840-014-9956-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved implant and postoperative lead performance in CRT-D patients implanted with a quadripolar left ventricular lead. A 6-month follow-up analysis from a multicenter prospective comparative study

Abstract: This multicenter study demonstrates that the use of a quadripolar LV lead results in significantly lower rates of lead-related problems and reduced procedural and fluoroscopic times for biventricular system implantation. This has important implications for LV pacing lead choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
2
25
1
3
Order By: Relevance
“…Quadripolar LV leads have been developed to overcome the main challenges to deliver LV stimulation at a nonapical LV site: PNS, lead stability, and a reliable LV pacing threshold . However, though some advantages in the implanting procedure have been observed, none of the studies have reported an improvement of patient outcome or of LV reverse remodeling owing to quadripolar leads. An observational registry by Behar et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quadripolar LV leads have been developed to overcome the main challenges to deliver LV stimulation at a nonapical LV site: PNS, lead stability, and a reliable LV pacing threshold . However, though some advantages in the implanting procedure have been observed, none of the studies have reported an improvement of patient outcome or of LV reverse remodeling owing to quadripolar leads. An observational registry by Behar et al .…”
Section: Discussionmentioning
confidence: 99%
“…The precise LV pacing location at TPS becomes a tradeoff with vein length and dislodgement risk, PNS (that is most frequent at mid‐to‐apical posterior‐lateral sites), and LVT. Compounding the necessity to elicit LV stimulation at mid and basal sites, the short‐spaced dipole is most frequently located at midventricle, to maximize PNS management at minimal compromise with LVT; indeed, LVT from all pacing electrodes was significantly lower compared to Quartet when a comprehensive PNS management strategy was achieved. Steroid elution at all four pacing electrodes helped to maintain a low and stable LVT (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional selective pacing configurations is an obvious advantage of quadripolar leads over bipolar leads. Studies have shown that quadripolar leads are associated with fewer complications, better LV capture threshold, greater improvement in LV ejection fraction (LVEF), and lower mortality rate . In this study, we sought to determine the advantages of quadripolar leads over bipolar leads in CRT outcomes at our center.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional bipolar (BIP) LV leads used in CRT systems have many shortcomings arising from their limited pacing configuration and limited ability for electronic repositioning. Quadripolar (QUAD) leads address these issues by offering improved pacing programmability to solve technical issues such as high pacing threshold and phrenic nerve stimulation (PNS), which, in turn, has been shown to reduce the need for reintervention associated with the LV leads . Reports comparing QUAD with BIP LV leads in cardiac resynchronization therapy defibrillator (CRT‐D) systems have shown that the use of QUAD LV leads results in lower rates of postimplant lead‐related complications, reduced procedural and fluoroscopic times, improved implant experience, better cardiovascular hemodynamics, lower healthcare utilization, and reduced mortality …”
Section: Introductionmentioning
confidence: 99%